2020
DOI: 10.3390/molecules25112466
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics Profile and Antioxidant Activity of Special Beers

Abstract: The antioxidant activity and polyphenols content of beer associated with its low alcohol content are relevant factors for an evaluation of the nutritional quality of beer. To investigate the effect of adding foods on the nutritional quality of beer, seven special beers that were commercially available and produced adding natural foods (walnut, chestnut, cocoa, honey, green tea, coffee, and licorice) during the fermentation process were analyzed for their polyphenols and flavonoids contents, phenolics profile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 68 publications
2
42
2
Order By: Relevance
“…Moreover, enhanced contents of phenolic acids such as ferulic, p-coumaric, syringic, and sinapic acids were found in the reinvented beers as compared with regular ones. This indicated that adding natural foods during the fermentation process resulted in the production of beers with improved antioxidant activity and superior phenolics profile [118]. Moreover, beers rich in phenolic antioxidants exhibits higher quality, more stable flavor and aroma, foam stability, and longer shelf life with respect to beers with lower antioxidant activity.…”
Section: Beer Enhancements and New Special Beer Designsmentioning
confidence: 99%
“…Moreover, enhanced contents of phenolic acids such as ferulic, p-coumaric, syringic, and sinapic acids were found in the reinvented beers as compared with regular ones. This indicated that adding natural foods during the fermentation process resulted in the production of beers with improved antioxidant activity and superior phenolics profile [118]. Moreover, beers rich in phenolic antioxidants exhibits higher quality, more stable flavor and aroma, foam stability, and longer shelf life with respect to beers with lower antioxidant activity.…”
Section: Beer Enhancements and New Special Beer Designsmentioning
confidence: 99%
“…In a study with Italian special beers, Nardini and Foddai (2020) [ 25 ] verified that the highest antioxidant activities were obtained for walnut beer followed by cocoa, chestnut, licorice, and coffee beers. This fact is in accordance with the higher polyphenols and flavonoids total contents observed in these same samples.…”
Section: Discussionmentioning
confidence: 99%
“…Craft beers produced with the addition of fruits, spices, or natural foods during the fermentation process have become very popular throughout the world, responding to consumer requests for new gustatory, olfactory, and visual stimuli. In this way, the addition of natural products to the beverage can increase the content of bioactive compounds and the oxidative stability of the beverage [ 11 , 25 ]. Despite that beer is considered a beverage rich in bioactive and antioxidant substances, such as phenolic compounds, a great amount of information can still be explored regarding the presence of these compounds in craft beers due to the diversity of substances present in the beverage [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors investigated changes in polyphenolic content in the production of beverages such as grape wines [8], sparkling wines [9], beer [10] or ciders [11]. Regarding meads, the literature contains research papers analyzing the composition and changes in the content of phenolic compounds under the influence of herbal or fruit additives [2] as well as under the influence of the yeast strain and heating process of the honey wort [12].…”
Section: Introductionmentioning
confidence: 99%